Evaluasi Penggunaan Obat pada Pasien Epilepsi di Poli Saraf RSD dr. Soebandi Jember - Dimas Ady Mahendra (Fakultas Farmasi, 2025)
Epilepsy is a chronic neurological disorder that requires long-term pharmacological management with close monitoring of Antiepileptic Drug (AED) use. Inappropriate use of AEDs can lead to Drug-Related Problems (DRPs), affecting the effectiveness and safety of therapy. This study aimed to evaluate the drug utilization profile, identify potential DRPs such as drug interactions and dosage suitability, and determine the characteristics of epilepsy patients at the Neurology Clinic of RSD dr. Soebandi Jember. This was a descriptive study with a retrospective approach, analyzing 224 medical records of epilepsy patients who met the inclusion criteria from January 1 to December 31, 2024. Data were analyzed for patient characteristics, AED usage patterns, dosage suitability based on the 2019 PERDOSSI guidelines, and potential drug interactions using the drugs.com database. The results showed that the majority of patients were female (124 patients; 55.35%) and in the 18-59 age group (215 patients; 95.98%). The drug utilization pattern was dominated by older generation AEDs, with phenytoin (150 patients; 66.96%), valproic acid (80 patients; 35.71%), and carbamazepine (63 patients; 28.13%) being the most frequently prescribed. Potential drug interactions were identified in 51 cases (22.72%), with moderate-level interactions being the most common. Dosage suitability issues were found, with 17 patients (7.59%) receiving a dose that was too low and 3 patients (1.34%) receiving a dose that was too high. In conclusion, the use of AEDs at the Neurology Clinic of RSD dr. Soebandi Jember relies on older generation drugs, and DRPs were identified. Therefore, enhanced monitoring of potential drug interactions and dose accuracy is crucial to minimize DRPs and improve therapeutic outcomes for epilepsy patients.
Reaploud Repository February_Hasyim
Keywords: Epilepsy; Antiepileptic Drugs; Drug Related Problem; Drug Use Evaluation; Drug Interactions